The relationship between attending alcohol serving venues nearby versus distant to one’s residence and sexual risk taking in a South African township - Eaton, Lisa A. (2013)
BACKGROUND: South Africa remains a country with one of the highest prevalence rates of HIV/AIDS at 18% among 15–49 year olds. Underdeveloped urban areas, or townships, are particularly hard hit by the HIV/AIDS epidemic. Alcohol use in these townships has been established as an important risk factor for HIV transmission. Likewise, alcohol serving venues (shebeens) have been identified as sites where substance abuse and sexual risk taking occur. However, little is known about how proximity of alcohol serving establishments (shebeens) to one's residence may be related to sexual risk-taking. METHODS: We surveyed 3,261 men and women attending shebeens in a township located in Cape Town, South Africa. We investigated the relationships between attending nearby (< 15 minute walk) versus distant (>15 minute walk) shebeens, and sex and substance abuse related risk-taking. RESULTS: Women who attended distant shebeens versus nearby shebeens relative to their residence were approximately twice as likely to report HIV positive status. Bivariate analyses demonstrated that these women were also more likely to report other sexually transmitted infections, greater numbers of sex partners, higher rates of alcohol and drug use, and seeking out new sex partners at shebeen. No differences in sex behavior, substance use or HIV/STI were identified among men. DISCUSSION: Proximity of shebeens appears to be an important contextual factor in explaining HIV/STI transmission risk-taking. Future studies should focus on how anonymity may be related to sexual risk and substance use behaviors among women in South African townships.